Sense-antisense gene pairs: sequence, transcription, and structure are not conserved between human and mouse - Wood, Emily J.; Chin-Inmanu, Kwanrutai; Jia, Hui; Lipovich, Leonard (Frontiers in Genetics, 2013)
Previous efforts to characterize conservation between the human and mouse genomes focused largely on sequence comparisons. These studies are inherently limited because they don't account for gene structure differences, which may exist despite genomic sequence conservation. Recent high-throughput transcriptome studies have revealed widespread and extensive overlaps between genes, and transcripts, encoded on both strands of the genomic sequence. This overlapping gene organization, which produces sense-antisense (SAS) gene pairs, is capable of effecting regulatory cascades through established mechanisms. We present an evolutionary conservation assessment of SAS pairs, on three levels: genomic, transcriptomic, and structural. From a genome-wide dataset of human SAS pairs, we first identified orthologous loci in the mouse genome, then assessed their transcription in the mouse, and finally compared the genomic structures of SAS pairs expressed in both species. We found that approximately half of human SAS loci have single orthologous locations in the mouse genome; however, only half of those orthologous locations have SAS transcriptional activity in the mouse. This suggests that high human-mouse gene conservation overlooks widespread distinctions in SAS pair incidence and expression. We compared gene structures at orthologous SAS loci, finding frequent differences in gene structure between human and orthologous mouse SAS pair members. Our categorization of human SAS pairs with respect to mouse conservation of expression as well as structure points to limitations of mouse models. Gene structure differences, including at SAS loci, may account for some of the phenotypic distinctions between primates and rodents. Genes in non-conserved SAS pairs may contribute to evolutionary lineage-specific regulatory outcomes.